PARTISIPASI ANGGOTA DAN PERMODALAN PADA KEBERHASILAN KOPERASI PRODUSEN TANI LEKMA MOKUPA DI KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Nursyawal Fitri; La Nalefo; Yoenita Jayadisastra; Arfiani Arfiani (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to determine the level of member participation, capital, and success of the Produsen Tani Lekma Mokupa Cooperative in Mokupa Village, Lambandia District, East Kolaka Regency. The population in this study consisted of 307 members of the Produsen Tani Lekma Mokupa Cooperative recorded in 2021, while the sample size was 39 members determined using the sloving formula. The Simple Random Sampling technique was employed for sampling. Data collection for this study involved the use of interviews, surveys, and documentation methods, as well as questionnaires as data collection instruments. The collected data was analyzed quantitatively using the class interval formula. The results indicate that the Produsen Tani Lekma Mokupa Cooperative was successful in business, members, and development. This success is classified as 'good' according to the Cooperative Success in Business, Members, and Development criteria. It is important to note that this evaluation is objective and based solely on the data presented. Member participation in organizational management, capital formation, and utilizing cooperative business services places it in the participating category. Additionally, the principal savings, mandatory savings, and voluntary savings of members of the Produsen Tani Lekma Mokupa Cooperative indicate that it is in the good category for capital.